2020
DOI: 10.1128/mbio.01985-20
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Methionine Synthase in a Fungal Pathogen Causes a Metabolic Imbalance That Impacts Cell Energetics, Growth, and Virulence

Abstract: There is an urgent need to develop novel antifungals to tackle the threat fungal pathogens pose to human health. Here, we have performed a comprehensive characterization and validation of the promising target methionine synthase (MetH). We show that in Aspergillus fumigatus the absence of this enzymatic activity triggers a metabolic imbalance that causes a reduction in intracellular ATP, which prevents fungal growth even in the presence of methionine. Interestingly, growth can be recovered in the presence of c… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 111 publications
2
29
0
Order By: Relevance
“…In mice, we found that the high doses of doxycycline required to downregulate fungal gene expression in the lungs were toxic to the animals, thus, we could not evaluate the effect on survival. Yet, we could show that the downregulation of metH produced a significant reduction in fungal burden, again similar to the reduction obtained when downregulating cyp51A [ 24 ]. Finally, we performed a structure-based virtual screening demonstrating that fungal methionine synthases have exclusive pockets that can be specifically targeted.…”
Section: Methionine Synthase Is Essential For a Fumigatus ...supporting
confidence: 74%
See 1 more Smart Citation
“…In mice, we found that the high doses of doxycycline required to downregulate fungal gene expression in the lungs were toxic to the animals, thus, we could not evaluate the effect on survival. Yet, we could show that the downregulation of metH produced a significant reduction in fungal burden, again similar to the reduction obtained when downregulating cyp51A [ 24 ]. Finally, we performed a structure-based virtual screening demonstrating that fungal methionine synthases have exclusive pockets that can be specifically targeted.…”
Section: Methionine Synthase Is Essential For a Fumigatus ...supporting
confidence: 74%
“…We firstly investigated the underlying reason for metH essentiality beyond methionine auxotrophy. We found that the absence of methionine synthase triggered a metabolic imbalance, likely due to a forced flow of glucose through the pentose phosphate pathway, that causes a decrease in cell energetics [ 24 ]. Using the tetOFF conditional promoter, we observed that the downregulation of metH in 8 h germinated conidia, as well as in 12 and 16 h-grown mycelia, sustainably halted fungal growth.…”
Section: Methionine Synthase Is Essential For a Fumigatus ...mentioning
confidence: 99%
“…Elevated abundance of zinc-dependent methionine synthase MetH/D was found with addition of 25 µM zinc, and was also found to be induced by heat shock in A. fumigatus [45], is either produced at high zinc due to an activity requirement, or is repressed under zinc-starved conditions. Interestingly there are strong links between the methyl/methionine cycle and GT biosynthesis via the utilization of SAM [46], and the conditional essentiality of MetH has recently been demonstrated [47].…”
Section: Discussionmentioning
confidence: 99%
“…Human pathogenic fungi express all proteinogenic amino acids [ 32 ] and antifungal compounds that inhibit enzymes of amino acid biosynthetic pathways show promising antifungal activity [ 33 , 34 ]. The virtual screening approach showed that inhibiting such enzymes in Aspergillus fumigatus leads to metabolic impairment that causes damage to ATP production, cell growth and virulence [ 34 ]. Here, S-adenosylmethionine synthase is downregulated in P. brasiliensis cells treated with AOS.…”
Section: Discussionmentioning
confidence: 99%